Antibodies Are Major Drivers of Protection against Lethal Aerosol Infection with Highly Pathogenic Burkholderia spp - Robert J. Hogan (American Society for Microbiology, 2019)
ABSTRACT Burkholderia pseudomallei and Burkholderia mallei are the causative agents of melioidosis and glanders, respectively. There is no vaccine to protect against these highly pathogenic bacteria, and there is concern regarding their emergence as global public health (B. pseudomallei) and biosecurity (B. mallei) threats. In this issue of mSphere, an article by Khakhum and colleagues (N. Khakhum, P. Bharaj, J. N. Myers, D. Tapia, et al., mSphere 4:e00570-18, 2019, https://doi.org/10.1128/mSphere.00570-18) describes a novel vaccination platform with excellent potential for cross-protection against both Burkholderia species. The report also highlights the importance of antibodies in immunity against these facultative intracellular organisms.